2013
DOI: 10.1002/jssc.201200887
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of schisandrin, schisandrol B, schisantherin A, deoxyschisandrin, and schisandrin B in rat plasma after oral administration of Shengmaisan formula by UPLCMS

Abstract: Shengmaisan (SMS) is a traditional Chinese medicine prescription widely used for the treatment of cardiovascular diseases in Asia. Its lignans are major components responsible for therapeutic action. A rapid and specific UPLC-Q-TOF/MS has been developed and validated for simultaneous quantification of the five main bioactive components, i.e. schisandrin, schisandrol B, schisantherin A, deoxyschisandrin, and schisandrin B, in rat plasma after oral administration of SMS. All calibration curves showed excellent l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…UHPLC-MS was validated for simultaneous quantification of the five main bioactive components (i.e., schisandrin, schisandrol B, schisantherin A, deoxyschisandrin, and schisandrin B) in rat plasma after oral administration of SMS [71]. Validation proved the repeatability of the method was good and recovery was satisfactory.…”
Section: Pharmacokineticsmentioning
confidence: 95%
“…UHPLC-MS was validated for simultaneous quantification of the five main bioactive components (i.e., schisandrin, schisandrol B, schisantherin A, deoxyschisandrin, and schisandrin B) in rat plasma after oral administration of SMS [71]. Validation proved the repeatability of the method was good and recovery was satisfactory.…”
Section: Pharmacokineticsmentioning
confidence: 95%
“…Recently, mass spectrometry (MS) has been recognized as a tool yielding huge potential for high‐throughput discovery of lead compounds from HM . MS is highly critical to drug discovery and preclinical development needs.…”
Section: Introductionmentioning
confidence: 99%
“…Professor Xijun Wang has been proved to be helpful to illuminate the effective constituents and metabolites of complex herbs and TCM prescription . It is suggested that only constituents absorbed into the blood have the opportunity to become active constituents after oral administration of TCM . Thus, developing a reliable and rapid analytical method for the characterization of the compounds from Radix Polygalae is necessary.…”
Section: Introductionmentioning
confidence: 99%